A carbon-thermal preparation method of nano TiC clusters for magnesium alloy with functions of melt purification and grain ultra-fining

CN122959563APending Publication Date: 2026-10-23XIAN TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611013697.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0013]本发明的目的是为了针对现有镁合金晶粒细化剂存在的形核核心易粗化、化学稳定性不足(如Al4C3易水解)、以及缺乏熔体净化协同功能的技术问题,提出一种兼具熔体净化与晶粒超细化功能的镁合金用纳米TiC团簇的碳热制备方法

Benefits of technology

1)首创“反应-净化”一体化机制。本发明变废为宝,利用传统工艺视为副产物的NaF-MgF2熔盐作为原位净化剂,利用其与氧化物夹杂的润湿性差异,在生成TiC的同时完成熔体深度除气除渣,显著简化了工艺流程,降低了生产成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959563A_ABST
    Figure CN122959563A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of non-ferrous metal smelting and organization control, and particularly discloses a carbon-thermal preparation method of nano TiC clusters for magnesium alloy, which has the functions of melt purification and grain ultra-fining, and has the following steps: taking sodium hexafluorotitanate (titanium ice crystal) with an ice crystal type crystal structure as a titanium source, taking nano carbon such as carbon nanotubes or graphene as a carbon source, preparing a core-shell type precursor through low-energy ball milling, and then performing a grading temperature control reaction in a magnesium melt, topological dissociation-reduction is first performed at 700-720 DEG C, then the temperature is increased to 755-785 DEG C and carbonization and cluster self-assembly are performed with the aid of a pulse electromagnetic field, so that string-bead-shaped or three-dimensional network-shaped nano TiC clusters are generated; and then, byproduct NaF-MgF2 molten salt is used to complete in-situ self-purification. The application is fundamentally different from existing refining technologies in terms of titanium source selection, reaction path, product configuration and function integration, and can simultaneously realize deep purification of a magnesium alloy melt and grain ultra-fining.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of non-ferrous metal smelting and microstructure control technology, specifically a carbothermic preparation method for magnesium alloys using nano-TiC clusters that combines melt purification and grain refinement. Background Technology

[0002] Magnesium alloys, as the lightest metallic structural materials currently used in engineering applications, have significant value in aerospace, automotive lightweighting, and electronic communications. However, the close-packed hexagonal crystal structure of magnesium alloys limits their room-temperature slip system and plastic processing capabilities. Furthermore, their wide crystallization temperature range, low thermal conductivity, and high shrinkage tendency make them prone to defects such as hot cracking and shrinkage porosity during solidification. Grain refinement is an effective means to simultaneously improve the strength and plasticity of magnesium alloys and has long been a core issue of concern in the field of magnesium alloy research.

[0003] Currently, methods for refining magnesium alloy grains mainly fall into two categories: one is physical external field refinement, such as electromagnetic stirring and ultrasonic treatment, which achieves refinement through forced convection and dendrite breakage. However, this method requires specialized equipment and has limited refining effect on thick cross-section castings. The other is chemical refinement, which involves adding refining agents to the magnesium melt to refine the grains by providing heterogeneous nucleation sites. Due to its simple process and significant effects, this method has become the mainstream in industrial applications. In the field of chemical refinement, several types of refining agents have been developed and reported: 1. Carbon-containing refining agent Carbon-based refining is one of the earliest discovered chemical refining methods for magnesium alloys. Studies have shown that adding carbon-containing substances (such as hexachloroethane C2Cl6, carbonates, carbon powder, etc.) to molten magnesium allows carbon atoms to react with aluminum in the melt to form Al4C3 and other compound particles, which can serve as heterogeneous nucleation sites for α-Mg. A patent has disclosed a Mg-Al-C intermediate alloy refining agent for magnesium alloys and its preparation method. The technical solution involves mixing aluminum powder and carbon powder and adding it to molten magnesium. Al4C3 particles are generated through the in-situ reaction of aluminum and carbon, serving as a heterogeneous nucleation substrate for α-Mg. This method utilizes the in-situ chemical reaction between aluminum and carbon to provide nucleation sites, achieving a refining effect to some extent. However, Al4C3 particles are highly susceptible to hydrolysis in aqueous service environments, generating methane gas and leaving corrosion pits, severely affecting the alloy's corrosion resistance and long-term service reliability.

[0004] A patented method for refining magnesium alloys through in-situ decomposition of magnesium carbonate involves adding magnesium carbonate powder to molten magnesium. The decomposition reaction of magnesium carbonate at high temperatures releases CO2 and MgO particles, with MgO acting as a nucleation core and the rising CO2 bubbles simultaneously acting as a degassing agent. This method combines the refining and degassing functions of the decomposition products. However, the vigorous and difficult-to-control decomposition process of magnesium carbonate can lead to concentrated gas release, causing melt splashing and burn-off, resulting in poor process safety. Furthermore, the generated MgO particles have a wide size distribution, with some particles being too large to effectively act as nucleation cores, leading to insufficient stability in the refining effect.

[0005] 2. Zirconium-containing refining agent Zirconium is widely recognized as the most effective grain-refining element for pure magnesium and aluminum-free magnesium alloys. Zirconium has very low solid solubility in magnesium; its addition allows it to form numerous fine, dispersed α-Zr particles in the melt, exhibiting extremely low lattice mismatch with α-Mg and resulting in highly efficient heterogeneous nucleation. Industrially, zirconium is primarily introduced by adding Mg-Zr master alloys. However, zirconium refining has strict compositional limitations: if aluminum is present in the magnesium alloy, zirconium preferentially reacts with aluminum to form Al3Zr compounds, poisoning the nucleation activity of α-Zr and consuming zirconium, leading to a complete loss of the refining effect. This limits the application of zirconium refining to the most widely used AZ series (Mg-Al-Zn) and AM series (Mg-Al-Mn) magnesium alloys.

[0006] 3. Calcium / Strontium-containing refining agent Calcium and strontium are commonly used to refine Mg-Al alloys. Calcium can form compounds such as Al₂Ca in magnesium melt, while strontium can form intermetallic compound particles such as Al₄Sr; both can serve as heterogeneous nucleation sites. However, the refining effect of calcium and strontium is sensitive to aluminum content, typically showing a significant refining effect only in magnesium alloys with low aluminum content, and its refining ability in high-aluminum alloys is significantly insufficient. Furthermore, excessive addition of calcium and strontium increases the alloy's brittleness and impairs its ductility.

[0007] 4. Contains rare earth refining agents The addition of rare earth elements (such as Ce, La, Y, Gd, etc.) to magnesium alloys can form Al-RE intermetallic compound particles, which can serve as nucleation nuclei during solidification. Existing patents disclose methods for refining magnesium alloys containing the rare earth element Y, utilizing the reaction of Y with Al to generate Al2Y particles as heterogeneous nucleation nuclei. The advantages of rare earth refining include good thermal stability, making it suitable for alloys used in high-temperature applications. However, its limitations include: the high cost of rare earth resources and their supply being heavily influenced by geopolitics, resulting in high refining agent costs; and the high lattice mismatch between some Al-RE compounds and α-Mg, leading to less than ideal nucleation efficiency.

[0008] In summary, the following common technical challenges remain in the field of magnesium alloy grain refinement, despite the various grain refinement methods described above: (1) It is difficult to balance the refining effect with the compatibility of the alloy system. Zirconium-containing refining agents have the best effect but are sensitive to aluminum and cannot be used in the most important AZ / AM series alloys; carbon-containing / calcium-containing / rare earth-containing refining agents are suitable for aluminum alloys, but the refining efficiency and adaptability to the process window still need to be improved.

[0009] (2) Insufficient thermal and chemical stability of the nucleation core. Al4C3 is easily hydrolyzed, the size of MgCO3 decomposition products is uncontrollable, and some intermetallic compounds are easily coarsened and dissolved during remelting or high-temperature service, resulting in a decline in the refining effect.

[0010] (3) Single function and lack of synergistic effect. Existing grain refinement methods usually only provide nucleation cores to achieve grain refinement, without contributing to the purification of the melt (degassing and slag removal). In industrial production, grain refinement and refining purification still need to be carried out in separate steps, which increases the complexity of the process and the production cost.

[0011] (4) Limited means of controlling the morphology and distribution of nucleation cores. Most heterogeneous nucleation particles generated by existing technologies are zero-dimensional equiaxed or blocky particles, with limited dispersion and pinning ability to grain boundaries. There is a lack of effective means to actively design and control the spatial configuration and distribution of particles.

[0012] Therefore, there is an urgent need to develop a novel composite treatment method that is suitable for aluminum-magnesium alloy systems, has both high refining efficiency and melt purification function, and can actively control the microstructure of the nucleation core. Summary of the Invention

[0013] The purpose of this invention is to address the technical problems of existing magnesium alloy grain refiners, such as easy coarsening of the nucleation core, insufficient chemical stability (e.g., easy hydrolysis of Al4C3), and lack of melt purification synergistic function. This invention proposes a carbothermic preparation method for magnesium alloy nano-TiC clusters that combines melt purification and grain refinement functions. To achieve the above objectives, the technical solution specifically adopted by the present invention is as follows: A method for preparing nano-TiC clusters for magnesium alloys, combining melt purification and grain refinement, utilizes sodium hexafluorotitanate (Na3TiF6, referred to as "titanium cryolite" in this invention) with a cryolite-type crystal structure as the titanium source and nano-carbon materials as the carbon source and structural template. It leverages the unique hierarchical dissociation-reduction mechanism of titanium cryolite in magnesium melt to achieve controlled and slow release of titanium atoms. The template effect of the nano-carbon materials guides TiC to orientedly assemble into beaded or three-dimensional network clusters along the template. Simultaneously, the byproduct NaF-MgF2 molten salt is actively designed as an in-situ purification medium, achieving melt self-purification while generating TiC clusters, ultimately integrating purification and grain refinement. The overall reaction formula (using magnesium melt as the reaction medium, 700–785℃) is as follows: Na3TiF6+ 3Mg + C→TiC + 3MgF2+ 3NaF Specifically, the following steps are included: Step 1: Construction of the precursor Sodium hexafluorotitanate (Na3TiF6) powder and nano-carbon materials are mixed at a Ti:C molar ratio of 1:1.02 to 1:1.10 and then subjected to low-energy ball milling under a protective atmosphere. The nano-carbon materials are at least one of multi-walled carbon nanotubes, few-layer graphene nanosheets, nanographite sheets, or carbon nanofibers. Preferably, the nano-carbon materials are multi-walled carbon nanotubes with an average diameter of 5–100 nm. The energy level of the low-energy ball milling is controlled below the mechanical alloying threshold, allowing the nano-carbon materials to physically coat or embed into the surface of the sodium hexafluorotitanate particles, thus obtaining a mixed precursor.

[0014] Step 2: Preparation of Magnesium Melt The magnesium alloy matrix raw material is heated to 660-690℃ to completely melt it, then heated to 700-720℃ and kept at that temperature until it is ready for use.

[0015] Step 3: Staged temperature-controlled reaction (1) Dissociation-reduction period: The mixed precursor is added to magnesium melt at 700-720℃ and kept at this temperature for 5-12 minutes. During this stage, the cryolite-type crystal structure of sodium hexafluorotitanate undergoes topological dissociation, sodium ions and some fluoride ions escape from the lattice in an orderly manner, and the [TiF6] octahedral framework undergoes topological contraction under the chemical action of magnesium, generating a metastable titanium-fluorine-magnesium intermediate complex.

[0016] (2) Carbonization-assembly stage: The melt is heated to 755-785℃ and a pulsed electromagnetic field is applied for assistance, and the temperature is maintained for 15-25 minutes. The parameters of the pulsed electromagnetic field are: current frequency 10-30 Hz, duty cycle 30%-60%, and magnetic field strength 0.05-0.2 T. During this stage, the metastable titanium-fluorine-magnesium intermediate complex dissociates and releases active titanium atoms. The active titanium atoms heterogeneously nucleate and carbonize in situ on the surface of the nano-carbon material, grow along the axial or in-plane direction of the nano-carbon material, and self-assemble to form quasi-one-dimensional beaded or three-dimensional network nano-TiC clusters formed by multiple interwoven beads.

[0017] Step 4: In-situ purification and separation After the reaction is complete, the pulsed electromagnetic field is stopped, the melt is cooled to 720–740°C, and allowed to stand for 8–15 minutes. The reaction byproduct NaF and MgF2 form a NaF-MgF2 binary molten salt system. This binary molten salt system floats in the melt and adsorbs oxide inclusions, forming slag.

[0018] Step 5: Scraping and Shaping After removing surface slag, the product is cast at 730–750°C to obtain a magnesium alloy product containing nano-TiC clusters.

[0019] As a preferred embodiment of the present invention, the process parameters of the low-energy ball mill are as follows: ball-to-material mass ratio of 5:1 to 8:1, rotation speed of 80 to 150 rpm, ball milling time of 20 to 60 min, the ball milling medium is zirconium oxide balls, the process control agent is anhydrous ethanol, and the amount of anhydrous ethanol added does not exceed 1% of the total mass of sodium hexafluorotitanate and nano-carbon material.

[0020] As a preferred embodiment of the present invention, the parameters of the pulsed electromagnetic field are: current frequency 10-30 Hz, duty cycle 30%-60%, and magnetic field strength 0.05-0.2 T.

[0021] In a preferred embodiment of the present invention, the mixed precursor is pressed into a block shape and then immersed in the magnesium melt before being added to the magnesium melt.

[0022] As a preferred embodiment of the present invention, the sodium hexafluorotitanate has a cryolite-type crystal structure, the crystal of which is composed of [TiF6] octahedral units and sodium ions filling the interstices of the octahedrons.

[0023] In a preferred embodiment of the present invention, the average particle size of the TiC particles in the nano-TiC cluster is 20-80 nm, and the average spacing between adjacent TiC particles is 5-50 nm.

[0024] The beneficial effects of this invention are as follows: 1) Pioneering an integrated "reaction-purification" mechanism. This invention turns waste into treasure by using NaF-MgF2 molten salt, which is considered a byproduct in traditional processes, as an in-situ purifying agent. By utilizing the difference in wettability between NaF-MgF2 molten salt and oxide inclusions, deep degassing and slag removal of the melt are completed simultaneously with the generation of TiC, which significantly simplifies the process and reduces production costs.

[0025] 2) Unique "staged slow release" kinetic control. Utilizing the unique cryolite-type crystal structure of titanium cryolite, staged slow release of titanium atoms is achieved through two-stage temperature control, avoiding local overheating and grain coarsening caused by the instantaneous exothermic reaction in traditional aluminothermic reactions, and ensuring the nanoscale size (20-80 nm) and uniform distribution of TiC particles.

[0026] 3) Clustering enhances refining efficiency. The “beaded” or “three-dimensional network” TiC clusters generated by nano-carbon templates have a larger specific surface area and a stronger grain boundary pinning effect compared to traditional zero-dimensional particles, which significantly improves refining efficiency. Moreover, the cluster configuration has excellent thermal stability during high-temperature service.

[0027] 4) The alloy system has good compatibility and high chemical stability. The formation of TiC does not depend on the aluminum content in the alloy, and it can be applied to aluminum-magnesium alloy systems, overcoming the compositional limitations of zirconium refining agents; at the same time, TiC does not undergo hydrolysis, overcoming the corrosion resistance defects of Al4C3 refining agents. Attached Figure Description

[0028] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 The images show the SEM morphology and elemental energy dispersive spectroscopy (EDS) results of the magnesium alloy sample prepared in Example 1. Figure 2 shows the EDS spot scan analysis results of the magnesium alloy sample obtained in Example 2; Figure 3 shows the EDS spot scan analysis results of the magnesium alloy sample obtained in Example 3. Detailed Implementation

[0029] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.

[0030] In the following embodiments: Sodium hexafluorotitanate (Na3TiF6) powder has a purity of ≥98.0%, and the nano-carbon material is multi-walled carbon nanotubes with a purity of ≥95.0% and an average diameter of 10–50 nm. The magnesium alloy matrix is ​​AZ91 magnesium alloy (specific composition range: Al 8.3–9.7%, Zn 0.35–1.0%, Mn 0.15–0.50%, balance Mg). All smelting processes are carried out under a protective atmosphere.

[0031] The microstructure of the samples was observed using scanning electron microscopy (SEM), and the composition of the particulate phase was analyzed using energy dispersive spectroscopy (EDS). Grain size was determined using the cut-off method, with at least 50 grains counted for each sample.

[0032] Example 1 This embodiment provides a method for preparing nano-TiC clusters for magnesium alloys that combines melt purification and grain refinement, including the following steps: (1) Construction of precursor: Sodium hexafluorotitanate powder and multi-walled carbon nanotubes were weighed at a molar ratio of Ti to C of 1:1.05 and ball-milled under argon protection with a ball-to-material mass ratio of 6:1, a rotation speed of 120 rpm, a ball-milling time of 40 min, a ball-milling medium of zirconia balls, and anhydrous ethanol (added at 0.8% of the total mass of materials) as the process control agent to obtain a mixed precursor of nano-carbon coated sodium hexafluorotitanate.

[0033] (2) Preparation of magnesium melt: Heat the AZ91 magnesium alloy matrix raw material to 680℃ to completely melt it, and then heat it to 710℃ and keep it warm for later use.

[0034] (3) Graded temperature control reaction: After the mixed precursor is pressed into a block, it is added to magnesium melt at 710°C and kept at that temperature for 8 minutes; then the melt is heated to 770°C and a pulsed electromagnetic field (current frequency 20 Hz, duty cycle 45%, magnetic field strength 0.1T) is applied and kept at that temperature for 20 minutes.

[0035] (4) In-situ purification and separation: Remove the pulsed electromagnetic field, cool the melt to 730°C, let it stand for 12 minutes, and the NaF-MgF2 binary molten salt generated by the reaction floats up and adsorbs oxide inclusions to form slag.

[0036] (5) Slag removal and molding: Remove surface slag and cast at 740℃ to obtain magnesium alloy products containing nano TiC clusters.

[0037] Example 2 The difference between this embodiment and Embodiment 1 is as follows: In step (1), the molar ratio of sodium hexafluorotitanate powder to multi-walled carbon nanotubes is 1:1.02; in step (3), the first-stage reaction temperature is 700℃, held for 5 minutes, the second-stage reaction temperature is 755℃, and the pulsed electromagnetic field parameters are: current frequency 10 Hz, duty cycle 30%, magnetic field strength 0.05 T, held for 15 minutes; in step (4), the settling temperature is 720℃, and the settling time is 8 minutes; in step (5), the casting temperature is 730℃. The remaining steps and parameters are the same as in Embodiment 1.

[0038] Example 3 The difference between this embodiment and Embodiment 1 is as follows: In step (1), the molar ratio of sodium hexafluorotitanate powder to multi-walled carbon nanotubes is 1:1.10; in step (3), the first-stage reaction temperature is 720℃, held for 12 minutes, the second-stage reaction temperature is 785℃, and the pulsed electromagnetic field parameters are: current frequency 30 Hz, duty cycle 60%, magnetic field strength 0.2 T, held for 25 minutes; in step (4), the settling temperature is 740℃, and the settling time is 15 minutes; in step (5), the casting temperature is 750℃. The remaining steps and parameters are the same as in Embodiment 1.

[0039] Example 4 The difference between this embodiment and Embodiment 1 is that in step (1), few-layer graphene nanosheets (average thickness of about 5 nm) are used instead of multi-walled carbon nanotubes as the nanomaterial. The remaining steps and parameters are the same as in Embodiment 1.

[0040] Comparative Example 1 The difference between this comparative example and Example 1 is that sodium hexafluorotitanate powder and nano-carbon materials are not added. The AZ91 magnesium alloy matrix raw material is directly melted and cast using the same melting process (680℃ melting → 710℃ holding → 770℃ holding for 20 min → 730℃ standing for 12 min → 740℃ casting) to obtain unrefined magnesium alloy products.

[0041] Comparative Example 2 The difference between this comparative example and Example 1 is that only multi-walled carbon nanotubes are added, and sodium hexafluorotitanate powder is not added. The remaining steps and parameters are the same as in Example 1.

[0042] Detection and characterization results (I) Microstructure and Energy Dispersive Spectroscopy Analysis Figure 1 The images show the SEM morphology and elemental energy dispersive spectroscopy (EDS) analysis results of the magnesium alloy sample prepared in Example 1. Figure 1It was found that a high-density white granular phase was dispersed in the alloy matrix. EDS surface scanning analysis showed that these white granular phases were rich in Ti and C elements, with an atomic ratio of Ti to C close to 1:1, confirming that the white granular phase was TiC. Energy dispersive spectroscopy (EDS) analysis confirmed the presence of high-density TiC particles in the alloy matrix.

[0043] Figure 2 shows the EDS spot scan analysis results of the magnesium alloy sample obtained in Example 2. Point-of-sight energy dispersive spectroscopy (EDS) analysis of the typical white particles in the matrix showed that the atomic ratio of Ti to C in these particles was close to 1:1, further confirming that the white particles were TiC. This indicates that the method of the present invention can form high-density, uniformly dispersed TiC particles in a magnesium alloy matrix.

[0044] Figure 3 shows the EDS spot scan analysis results of the magnesium alloy sample prepared in Example 3. Similar to Figure 2, the EDS spot scan confirmed that the white particles in the alloy matrix are TiC, indicating that the method of the present invention can form high-density, uniformly dispersed TiC particles in the magnesium alloy matrix.

[0045] (II) TiC Particle Size Statistics right Figure 1 Statistical analysis of the TiC particle size in Figure 3 shows that the average particle size of TiC particles is 100 nm and the average spacing between adjacent TiC particles is 260 nm.

[0046] (III) Grain Refinement Effect To verify the grain refinement effect of the method of the present invention on magnesium alloys, Comparative Example 1 was set as a blank control. Comparative Example 1 used the same magnesium alloy matrix composition and melting process as Example 1, but did not add titanium cryolite and nano-carbon precursors, and only underwent the same melting, holding and casting process. The metallographic structure of the as-cast samples of Example 1 and Comparative Example 1 was observed, and the average grain size was measured by the cross-section method. Twenty fields of view were randomly selected from each sample for statistical analysis.

[0047] The results showed that the unrefined as-cast microstructure of Comparative Example 1 was coarse, with an average grain size of 386 μm (range 280~510 μm). The grains exhibited coarse equiaxed or well-developed dendritic morphology, with some columnar crystals extending more than 1 mm. The as-cast microstructure of Example 1 treated with the method of this invention was significantly refined, with an average grain size of 52 μm (range 28~85 μm), a reduction of 86.5% compared to Comparative Example 1. The grain morphology changed from coarse dendritic to fine and uniform equiaxed grains, with no obvious dendritic segregation or abnormally large grains observed. This indicates that the method of this invention utilizes in-situ generated beaded or three-dimensional network-like nano-TiC clusters as heterogeneous nucleation cores for α-Mg, which can significantly refine magnesium alloy grains with excellent refining effect.

[0048] (iv) Purification effect To verify the purification effect of the method of the present invention on magnesium melt, metallographic observation and quantitative analysis were performed on samples of the melt purified in situ by NaF-MgF2 binary molten salt in Example 1. The sampling method was as follows: After the first-stage reaction was completed (i.e., after adding the precursor and holding at temperature for 5-12 minutes, but before carbonization), the first sample was taken from the middle of the melt and recorded as the "sample before purification"; after the purification was completed and before slag removal, the second sample was taken from the same depth and recorded as the "sample after purification". After polishing, 20 fields of view were randomly selected using a scanning electron microscope (SEM) backscattered electron image, and the area fraction of oxide inclusions was statistically analyzed.

[0049] The results showed that after in-situ purification with NaF-MgF2 binary molten salt, the area fraction of oxide inclusions in the melt decreased from 0.62% (range 0.45%~0.85%) before treatment to 0.11% (range 0.06%~0.18%), a reduction of 82.3%. Metallographic observation showed that before purification, dark-colored blocky or strip-shaped inclusions with a size of 1~5 μm (confirmed by energy dispersive spectroscopy as MgO and a small amount of Al2O3) were unevenly distributed in the matrix. After purification, the number of inclusions in the sample was significantly reduced, and the size of the remaining inclusions was generally less than 1 μm, with a sparse distribution. This indicates that the method of the present invention utilizes the dual effects of wetting and capturing and chemical dissolution of the byproduct NaF-MgF2 molten salt during the flotation process to efficiently remove oxide inclusions in magnesium melt, demonstrating a good melt purification effect.

[0050] Comprehensive analysis of Examples 1-4 shows that the method of the present invention can successfully generate nano-TiC clusters in situ in a magnesium alloy matrix. The TiC particles are uniformly dispersed in the matrix in a quasi-one-dimensional beaded or three-dimensional network structure formed by multiple bundles of beads. At the same time, the reaction byproduct molten salt can effectively remove oxide inclusions in the melt, realizing the integration of grain refinement and melt purification.

[0051] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A carbothermic preparation method for magnesium alloy nano-TiC clusters that combines melt purification and grain refinement functions, characterized in that, Includes the following steps: Sodium hexafluorotitanate powder and nano-carbon materials were mixed at an atomic ratio of Ti to C of 1:1.02 to 1:1.10 and ball-milled under an inert atmosphere to obtain a mixed precursor in which nano-carbon is coated or attached to the surface of sodium hexafluorotitanate. The magnesium alloy matrix material is heated to 660-690℃ in a protective atmosphere to melt, and then heated to 700-720℃ and held at that temperature. The mixed precursor is added to magnesium melt at 700-720°C and held for 5-12 minutes. Heat the melt to 755–785°C, apply a pulsed electromagnetic field, and hold for 15–25 minutes. Remove the pulsed electromagnetic field, cool the melt to 720-740℃, let it stand for 8-15 minutes, and the reaction will produce NaF-MgF2 binary molten salt; After removing the slag from the surface of the melt, it is cast into shape at 730-750℃.

2. The carbothermic preparation method according to claim 1, characterized in that, The nano-carbon material is at least one of multi-walled carbon nanotubes, few-layer graphene nanosheets, nano-graphite sheets, or carbon nanofibers, with an average diameter of 5–100 nm.

3. The carbothermic preparation method according to claim 1, characterized in that, The process parameters for the low-energy ball mill are as follows: ball-to-material mass ratio of 5:1 to 8:1, rotation speed of 80 to 150 rpm, ball milling time of 20 to 60 min, ball milling media of zirconia balls, process control agent of anhydrous ethanol, and the amount of anhydrous ethanol added does not exceed 1% of the total mass of sodium hexafluorotitanate and nano-carbon materials.

4. The carbothermic preparation method according to claim 1, characterized in that, The parameters of the pulsed electromagnetic field are: current frequency 10-30 Hz, duty cycle 30%-60%, and magnetic field strength 0.05-0.2 T.

5. The carbothermic preparation method according to claim 1, characterized in that, The mixed precursor is pressed into a block shape and then immersed in the magnesium melt before being added to the magnesium melt.

6. The carbothermic preparation method according to claim 1, characterized in that, The NaF-MgF2 binary molten salt floats in the melt and adsorbs oxide inclusions.

7. The carbothermic preparation method according to claim 1, characterized in that, The nano-TiC clusters prepared by the method are quasi-one-dimensional beaded structures or three-dimensional network structures formed by multiple interwoven beaded bundles.

8. The carbothermic preparation method according to claim 1, characterized in that, The sodium hexafluorotitanate has a cryolite-type crystal structure, and its crystal is composed of [TiF6] octahedral units and sodium ions filling the interstices of the octahedrons.

9. A magnesium alloy, characterized in that, The magnesium alloy is prepared by the carbothermal preparation method according to any one of claims 1 to 8, wherein quasi-one-dimensional beaded or three-dimensional network nano-TiC clusters are dispersedly distributed in the matrix of the magnesium alloy.

10. The magnesium alloy according to claim 9, characterized in that, The average particle size of the TiC particles in the nano-TiC clusters is 20–80 nm, and the average spacing between adjacent TiC particles is 5–50 nm.